STATISTICAL CONVERGENCE AND STRONG p-CESARO SUMMABILITY OF ORDER ? IN SEQUENCES OF FUZZY NUMBERS - Altinok, H.; Altin, Y.; Isik, M. (Univ Sistan & Baluchestan, 2012)
In this study we introduce the concepts of statistical convergence of order beta and strong p-Cesaro summability of order beta for sequences of fuzzy numbers. Also, we give some relations between the statistical convergence of order beta and strong p-Cesaro summability of order beta and construct some interesting examples.
Keywords: Fuzzy number; Statistical convergence; Cesro summability